2019
DOI: 10.2478/inmed-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Longitudinal Strain Evaluated by 2D Speckle Tracking Echocardiography Can Identify Patients with Heart Failure with Preserved Ejection Fraction

Abstract: The aim of the paper is to investigate the utility of left atrial longitudinal strain (LALS) in the diagnosis of heart failure with preserved ejection fraction (HFpEF) when left ventricular diastolic function is indeterminable and the assessment of natriuretic peptides is not routinely performed.Method. The study included 180 patients with signs and symptoms suggestive of non-acute heart failure, examined clinically and echocardiographically, both conventionally and via speckle tracking method.Results. 33 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Another study evaluated left atrial function using 2-D speckle tracking echocardiography and found that left atrial strain was significantly decreased in patients with HFpEF compared with that in controls. The study also found that left atrial strain was independently associated with a higher risk of adverse events, including hospitalization and mortality [ 39 ].…”
Section: Imagingmentioning
confidence: 99%
“…Another study evaluated left atrial function using 2-D speckle tracking echocardiography and found that left atrial strain was significantly decreased in patients with HFpEF compared with that in controls. The study also found that left atrial strain was independently associated with a higher risk of adverse events, including hospitalization and mortality [ 39 ].…”
Section: Imagingmentioning
confidence: 99%